2023
DOI: 10.3390/ma16124399
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cryogenic Treatment Process on the Performance of 51CrV4 Steel

Abstract: The working load on automotive components is continuously rising, and the mechanical performance requirements for component materials are rising along with the growth trend toward light weight and high dependability in automobiles. In this study, the response characteristics of 51CrV4 spring steel were taken to be its hardness, wear resistance, tensile strength, and impact toughness. Prior to tempering, cryogenic treatment was introduced. Through the Taguchi method and gray relational analysis, the ideal proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…The cryogenic treatment of H13 hot work die steel has revealed that the retained austenite transforms into martensite during the cryogenic treatment, and that a large number of dispersed carbides precipitate from the matrix, which is helpful to improve the hardness and thermal fatigue resistance of the material [18]. The yield limit of 51CrV4 spring steel can be increased by 14.95% and the wear mass loss can be reduced by 43.32% by introducing cryogenic treatment before tempering [19]. The test results on W6 high-speed steel after cryogenic treatment at −150 • C for 12 h have shown that the formation of fine carbides, uniformly distributed in the steel, reduces the dislocation stress and ultimately affects the macroscopic residual stress [20].…”
Section: Introductionmentioning
confidence: 99%
“…The cryogenic treatment of H13 hot work die steel has revealed that the retained austenite transforms into martensite during the cryogenic treatment, and that a large number of dispersed carbides precipitate from the matrix, which is helpful to improve the hardness and thermal fatigue resistance of the material [18]. The yield limit of 51CrV4 spring steel can be increased by 14.95% and the wear mass loss can be reduced by 43.32% by introducing cryogenic treatment before tempering [19]. The test results on W6 high-speed steel after cryogenic treatment at −150 • C for 12 h have shown that the formation of fine carbides, uniformly distributed in the steel, reduces the dislocation stress and ultimately affects the macroscopic residual stress [20].…”
Section: Introductionmentioning
confidence: 99%